Teacher Perceptions of the Use of Socioscientific Issues in Science Learning in Middle Schools of Tanjung Sakti District PUMI and Tanjung Sakti District PUMU - Legy Gustiawan*; Muhamad Yusup; Kistiono Kistiono (Program Studi Magister Pendidikan IPA Program Pascasarjana Universitas Syiah Kuala, 2023)
Currently, there are already many countries that have revised their science curricula to be sure effective science learning environments. Blessing in this revision, socioscientific issues are integrated into the curriculum. Their presence has brought about the need to know what socioscientific environmental problems exist. The research conducted aims to describe the perceptions of junior high school science teachers regarding the use of socioscientific issues in science learning at SMP Tanjung Sakti PUMI and Tanjung Sakti PUMU districts. In this descriptive quantitative study, data were collected using 15 items of statements with a questionnaire in the form of a Likert scale. The research subjects were seventeen science teachers from Tanjung Sakti Public Middle School 1 PUMI, Tanjung Sakti Public Middle School 2 PUMI, Tanjung Sakti Public Middle School 3 PUMI, Tanjung Sakti Public Middle School 4 PUMI, Tanjung Sakti Public Middle School 1 PUMU, Tanjung Sakti Middle School 2 PUMU, Middle School Mumammadiyah Batu Rancing, SMP PUMI Xaverius Tanjung Sakti. The study results show that science teachers have very positive perceptions or agree to use socioscientific issues in science learning. This study shows that science teachers' perceptions about socioscientific issues are well received, and the use of socioscientific issues is very impressive in the science learning process.